Is the teacher is a person with a public function? On the margin of a legislative error (Belügyi Szemle, 2024)
Aim: The study presents the controversial legislative amendment that has made it controversial from 1 January 2024 whether teachers can be considered as public servants.Methodology: The study uses logical, taxonomic and historical analysis.Findings: In the light of this, it is difficult to identify which persons fall into this category. It is difficult to determine which persons are considered to be performing a public duty. However, teachers, as their work as lecturerers and educators is a fundamental national value, should be included, regardless of whether this is explicitly stated in other legislation.Value: The study concludes that the judiciary is justified in considering teachers as performing a public task even if there was a period between 1 January 2024 and 10 May 2024 when the Public Education Act did not explicitly state this.